Janibacter species with evidence of genomic polymorphism isolated from resected heart valve in a patient with aortic stenosis - Lile Malania; Ying Bai; Kamil Khanipov; Marika Tsereteli; Mikheil Metreveli; David Tsereteli; Ketevan Sidamonidze; Paata Imnadze; Yuriy Fofanov; Michael Kosoy (MDPI AG, 2019)
We report isolation and identification of two strains of bacteria belonging to the genus Janibacter from a human patient with aortic stenosis from a rural area of the country of Georgia. The microorganisms were isolated from aortic heart valve. Two isolates with slightly distinct colony morphologies were harvested after sub-culturing from an original agar plate. Preliminary identification of the isolates is based on amplification and sequencing of a fragment of 16SrRNA. Whole genome sequencing was performed using the Illumina MiSeq instrument. Both isolates were identified as undistinguished strains of the genus Janibacter. Characterization of whole genome sequences of each culture has revealed a 15% difference in gene profile between the cultures and confirmed that both strains belong to the genus Janibacter with the closest match to J. terrae. Genomic comparison of cultures of Janibacter obtained from human cases and from environmental sources presents a promising direction for evaluating a role of these bacteria as human pathogens.